Finger Exoskeleton in Simple Motor Rehabilitation Therapy on Arm and Hand Muscle Ability of Post-Stroke Sufferers - Puspa Wardhani; Irma Triyani; Fakrul Ardiansyah; Filomena Adelaide de Matos (JURNAL INFO KESEHATAN, 2021)
Post-stroke sufferers will generally experience weakness on one side of the body, balance, vision, sensory, motor, and cognitive. In West Kalimantan, the estimated stroke sufferer in 2013 was 25,195 people. Based on data from the Public Hospital of Dr. Soedarso Pontianak shows a significant increase from January 2018 to December 2018 totaling 722 people. The research objective was to assess the effectiveness of the finger exoskeleton tool in simple motor therapy on the ability of the client's arm and hand muscles after a stroke. This study used a quantitative approach with a quasi-experimental design. Pre-test and Post-test Nonequivalent Control Group with two groups, which were the control group of 12 people and the intervention group of 12 people with finger exoskeleton tools. The statistical test used was the independent t test and paired t test. Measurement of muscle ability with the Action Research Arm Test. Analysis of the difference in total scores between before and after treatment in the intervention group using Paired T-Test obtained a p-value of 0.000 (p value <0.05) and in the control group using the Wilcoxon test a p-value of 0.016 (p value <0.05). It shows that there is a significant difference in the total score between before and after finger exoskeleton therapy and range of motion. Intervention of finger exoskeleton assistive devices in simple motor rehabilitation therapy is effective in increasing the ability of the client's arm and hand muscles after stroke. It is recommended to make another finger rehabilitation tool with a more optimal design according to the parameters, which are the severity of the client after stroke, subject kinematics, control of movement torque and adaptation between the subject and the robotic device used.